Family Farm Resilience during the COVID-19 Pandemic in Indonesia: Case Studies on Organic and Conventional Farming - Saleh, Rahmat; Sitohang, Marya Yenita; Ningrum, Vanda; Latifa, Ade; Ibnu, Fitranita; Fatoni, Zainal (Jurnal Penyuluhan, 2024)
The COVID-19 pandemic has brought additional stressors to Indonesian family farms, which are already subject to drought, flood, landslide, pest attack, and market price fluctuations. This study aims to analyse family farms’ resilience to the stressors caused by the COVID-19 pandemic using Henry’s family resilience model. Applying a qualitative approach, this study collected data using focus group discussions in two villages in East Java and a village in Center Java. The data was analysed using thematic analysis. We discovered that stressors related to the COVID-19 pandemic are lower demand on agricultural products and lower income among farmers. Organic and conventional farmers have different protection and vulnerability factors. Organic farmers are able to reach buyers directly using social media amid COVID-19 restrictions while conventional farmers still rely on sales through middlemen. The adaptive process of farming families is influenced by social psychological factors within the family such as meaning, emotion, control, and maintenance systems. This study suggests that family farmers have to be empowered in terms of their innovative production in current stressors and increase their access to the market as a priority for agricultural extension programmes.